Livelihood Sustainability Assessment of Payment for Ecosystem Services Providers in Cidanau Watershed, Banten Province - Biru, Muhammad Diheim; Karuniasa, Mahawan; Mizuno, Kosuke (Institut Pertanian Bogor (IPB University), 2023)
The payment for ecosystem services (PES) scheme in the Cidanau Watershed, Banten Province, Indonesia has not yet quantified and reviewed its livelihood impacts on its providers after two decades of implementation. Therefore, this study maps the livelihood sustainability of PES farmers and non-PES farmers in the Cidanau Watershed using capital indexes based on the five livelihood capital assets of the DFID’s sustainable livelihood framework. The research used a quantitative method to formulate the livelihood capital indexes (LCI) as approximates to the subjects’ livelihood sustainability based on their livelihood information and draws implications from the results thereof. A total of 168 agroforestry farmers both from PES and non-PES groups were interviewed across 12 villages in the upstream area. The results show that both PES and non-PES groups share the same pattern of capital assets sustainability with the PES group having a slightly higher human capital asset. The overall LCI calculated for the PES and non-PES groups are 0.445 and 0.48, respectively. The livelihood of both groups is deemed as not yet sustainable. The farmers would have to develop their financial and human assets to attain more sustainable livelihoods and prepare themselves for adopting new types of PES in the future.